Effect of post-activation potentiation on the force, power and rate of power and force development of the upper limbs in mixed martial arts (MMA) fighters, taking into account training experience - Alan Langer; Angelina Ignatieva; Patricia Fischerova; Magdalena Nitychoruk; Artur Golas; Adam Maszczyk (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2022)
Introduction. The aim of the study is to determine the optimal load for generating the highest value of force, power and the rate of power and force development (RFD and RPD) in the upper limb of mixed martial arts (MMA) fighters with the use of activation and explosive exercises. The training period of MMA players was included in the research. Material and Methods: Twenty-nine MMA fighters participated in the study and were divided into two groups depending on the length of their training period (under and over 5 years). The subjects did 2 ballistic push-ups before the study and after-wards they performed 5 repetitions of press dumbbells while lying down with an increasing load: 50% 1RM, 65% 1RM and 80% 1RM. The rest was 4 minutes. All ballistic push-ups were performed on ForceDecks, and the data was analysed using the manufacturer's software. To compare differences between the groups, one-way ANOVA and post-hoc test were used. T-Student test was used to deter-mine the differences within the groups. Results: Amateurs obtained greater force and RPD results after the activation exercise performed at 50% 1RM, while power and RFD at 65% 1RM. For professionals, the highest force was achieved with a load of 80% 1RM, power at 50% 1RM, and RFD and RPD at 80% 1RM. Statistically significant differences between the groups were observed before and after each trial in force and RPD. The power did not statistically differ only after the load of 65% 1RM. In RFD, no statistically significant differences were found between the studied groups. Conclusions: Competitors with longer training experience should use a greater load in an activation exercise than competitors with shorter training experience.